2021
DOI: 10.3233/jpd-202215
|View full text |Cite
|
Sign up to set email alerts
|

Slow Wave Sleep and EEG Delta Spectral Power are Associated with Cognitive Function in Parkinson’s Disease

Abstract: Background: Cognitive and sleep dysfunction are common non-motor symptoms in Parkinson’s disease (PD). Objective: Determine the relationship between slow wave sleep (SWS) and cognitive performance in PD. Methods: Thirty-two PD participants were evaluated with polysomnography and a comprehensive level II neurocognitive battery, as defined by the Movement Disorders Society Task Force for diagnosis of PD-mild cognitive impairment. Raw scores for each test were transformed into z-scores using normative data. Z-sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…We are aware of two previous studies that compared SWA to cognition in PD, with inconsistent findings. While a detailed sleep EEG analysis in 68 PD patients reported no association of cognitive impairment or decline with SWA (NREM delta power) (17), a recent study linked frontal SWA to global cognition in 32 PD patients (18). Compared to these studies, our analysis includes a larger sample (n = 140) of non-demented PD patients and 1-Hz-segmentation of regional SWA.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We are aware of two previous studies that compared SWA to cognition in PD, with inconsistent findings. While a detailed sleep EEG analysis in 68 PD patients reported no association of cognitive impairment or decline with SWA (NREM delta power) (17), a recent study linked frontal SWA to global cognition in 32 PD patients (18). Compared to these studies, our analysis includes a larger sample (n = 140) of non-demented PD patients and 1-Hz-segmentation of regional SWA.…”
Section: Discussionmentioning
confidence: 89%
“…A detailed sleep EEG analysis reported no association of SWA with cognitive impairment in PD patients, but instead highlighted the importance of other sleep EEG alterations over posterior derivations (17). In contrast, a recent study linked SWA, a priori selected from frontal derivations, to global cognition, but the sample included only 32 PD patients (18). Therefore, the aim of our study was to clarify the relationship of SWA with cognition in PD by analyzing SWA and its regional variation in a larger sample of non-demented PD patients.…”
Section: Introductionmentioning
confidence: 95%
“…A growing body of research confirms that auditory stimulation ( 150 ), transcranial direct current stimulation ( 151 ), and medication ( 152 ) are all effective in improving memory function by enhancing slow waves of sleep ( 153 ). Slow-wave sleep is not only used for memory enhancement, but has also been widely used to improve cognitive function in patients with mental illness ( 154 , 155 ) and for sensory-motor recovery in stroke patients ( 156 ). Recent studies have shown that enhancing SWS in healthy individuals profoundly affects the connections between the endocrine and autonomic nervous systems ( 157 ), opening up a wide range of potential applications for enhancing SWS.…”
Section: Discussionmentioning
confidence: 99%
“…SWS is not only a major contributor to neurophysiological processes such as memory and attention, but it is also crucial for brain metabolite clearance ( 39 , 45 ). Moreover, deeper sleep relates to slower motor progression and better cognitive performance in PD ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%